Pediatric Charcot-Marie-Tooth disease: A case report and diagnostic challenges - Babu, Sarath; George, Ditty; Vakayil, Johny (Indian Journal of Case Reports, 2024)
Charcot-Marie-Tooth (CMT) disease is a hereditary motor sensory neuropathy affecting about one in 2500 individuals that is characterized by progressive weakness and loss of touch sensation affecting different parts of the body. Despite its significant genetic heterogeneity, CMT is rarely reported in the Indian literature. We report a 10-year-old boy with CMT presented with severe calf pain, bilateral pes cavus deformity, and areflexia. His mother also had similar symptoms, and the diagnosis was confirmed by neuroimaging and nerve conduction studies. This highlights the importance of considering CMT disease in patients with progressive muscle weakness and deformities, especially with a family history of similar symptoms.